Nicole Oresme. Le livre de Yconomique d'Aristote. Critical edition, introduction and English translation by Albert Douglas Menut. - Páramo Pomareda, Jorge; Páramo Pomareda, Jorge (Thesavrvs, 2023)
Versión de Maistre Nicole Oresme de las Occonomica del corpus aristotélico.